A 3D printed high-strength oral denture base and preparation method thereof

The 3D printing technology has prepared a composite material with titanium oxide composite microspheres coated chitosan and surface-modified boron nitride nanotubes coated nanosilver particles, which has solved the problem of insufficient strength and antibacteriality of existing denture base materials. It achieves efficient and long-term mechanical and antibacterial properties, improving patients' oral health and quality of life.

CN118986751BActive Publication Date: 2025-02-14CHONGQING XINLEMEI MEDICAL TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411068118.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2025-02-14
Estimated Expiration
2044-08-06

AI Technical Summary

Technical Problem

The existing oral denture base materials have insufficient performance in terms of strength and antibacterial properties, making it difficult to meet the needs of high-performance denture bases.

Method used

Using 3D printing technology to prepare a composite material composed of titanium oxide composite microspheres coated chitosan and surface-modified boron nitride nanotube coated nanosilver particles, which improves mechanical properties and antibacterial through the distribution of porous structures and nanowires. Efficiency and long-term antibacterial through the sustained release properties of chitosan.

Benefits of technology

It significantly improves the mechanical properties and antibacterial efficiency of the denture base, extends the service life, reduces the risk of oral infection, and improves the oral health and quality of life of patients.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118986751B_ABST
    Figure CN118986751B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of denture base materials, and provides a 3D printing high-strength oral denture base and a preparation method thereof. The denture base is prepared from the following components: titanium oxide composite microspheres coated with chitosan, surface modified boron nitride nanotubes coated with nano-silver particles, acrylic resin, polyetheretherketone, anhydrous ethanol, defoamer, dispersant, and photoinitiator. Preparation method: S1. Disperse fillers, and prepare a uniform mixed solution by ultrasonic and mechanical stirring; S2. Prepare a resin base liquid, add acrylic resin, polyetheretherketone and other materials and stir evenly; S3. Print and form, and use a DLP light-curing 3D printer to print the denture base; S4. Finishing, including demoulding, cooling and surface grinding treatment, finally obtaining a finished denture base. The present invention solves the strength and antibacterial problems of the denture base by combining titanium oxide composite microspheres with chitosan coating layers and surface modified boron nitride nanotubes coated with nano-silver particles, respectively, and has a wide range of application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of denture base materials, and in particular to a 3D printed high-strength oral denture base and a preparation method thereof. Background Art

[0002] With the rapid development of 3D printing technology, the demand for personalized oral dentures is growing. Compared with traditional denture manufacturing processes, 3D printing technology has the advantages of high design freedom, short production cycle, and high material utilization rate, and has become an important development direction in the field of oral restoration. As the key supporting structure of the restoration, the oral denture base needs to have excellent mechanical strength and rigidity to withstand the stress during chewing and maintain the morphological stability of the restoration. At the same time, the denture base material should also have good toughness and fatigue resistance to adapt to the dynamic stress changes in the oral environment and extend the service life of the restoration. High-strength denture base materials can not only improve the load-bearing capacity and stability of the restoration, but also achieve a lighter and thinner restoration design and improve the patient's wearing comfort. In addition, the oral environment is complex and changeable, and it is an ideal place for a variety of pathogenic microorganisms to colonize. The bacterial growth on the surface of the denture base not only causes oral diseases such as tooth decay and periodontitis, but also may induce systemic infection and threaten the health of patients. Therefore, denture base materials also need to have excellent antibacterial properties, which can effectively inhibit the adhesion of bacteria on the surface of the restoration and the formation of biofilm, maintain the balance of oral microecology, and reduce the risk of complications such as secondary caries and denture stomatitis. The development of 3D printed denture base materials with both high strength and antibacterial properties is of great significance for improving the quality of oral restorations, extending the service life of restorations, and protecting patients' oral health.

[0003] At present, although many advances have been made in denture base materials, the strength and antibacterial properties of denture base materials can be significantly improved by adding ceramic fillers, optimizing molding methods and parameters, etc. However, there are still some shortcomings. (1) The strength of denture base materials still needs to be further improved to meet more stringent usage environment requirements. For example, Chinese patent No. CN113181061A discloses a solution for using titanium dioxide particles to enhance the strength of denture bases. However, since conventional ceramic particles are usually spherical and have poor chemical compatibility with the resin matrix, the addition of traditional conventional ceramic particles has limited effect on the enhancement of denture bases. (2) The realization and maintenance of antibacterial properties is still one of the technical difficulties. Although most denture base designs take antibacterial properties into consideration, they are usually simply added to the denture base. For example, Chinese patent No. CN111789771A discloses a solution for adding antibacterial agents to denture bases, but due to insufficient material stability, sustained release problems, biocompatibility considerations and manufacturing process limitations. These factors cause the antibacterial agents to easily degrade during long-term use, increasing the risk of oral infection, worsening oral health, shortening the service life of dentures, and reducing the quality of life of patients. Therefore, it is crucial to develop denture base materials and technologies with long-term antibacterial properties. In summary, the current denture base materials still face many challenges in terms of strength and antibacterial properties. In order to further improve the performance of current denture base materials, it is necessary to develop a new type of denture base that has both high strength and antibacterial properties to meet the needs of high-performance denture bases. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a 3D printed high-strength oral denture base and a preparation method to solve the problem that the current oral denture base has insufficient performance in terms of strength, antibacterial properties, etc.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A 3D printed high-strength oral denture base is made of the following components by weight: 5 to 10 parts of titanium oxide composite microspheres coated with chitosan, 4 to 9 parts of surface-modified boron nitride nanotubes coated with nanosilver particles, 80 to 110 parts of acrylic resin, 4 to 10 parts of polyetheretherketone, 20 to 30 parts of anhydrous ethanol, 1 to 3 parts of a defoaming agent, 2 to 5 parts of a dispersant, and 2 to 4 parts of a photoinitiator.

[0009] Furthermore, the preparation method of the titanium oxide composite microspheres coated with chitosan is as follows: by weight, 3 to 8 parts of chitosan are dissolved in 20 to 30 parts of a 2% acetic acid aqueous solution, stirred for 15 to 30 minutes, then 10 to 20 parts of titanium oxide composite microspheres are added, ultrasonically treated for 10 to 20 minutes, and then vacuum impregnated for 15 to 30 minutes, and finally vacuum dried at room temperature for 10 to 18 hours, and this vacuum impregnation-vacuum drying cycle is repeated 3 times. After all cycles are completed, the product is washed with deionized water. During the washing process, it is necessary to ensure that the deionized water completely submerges the titanium oxide composite microspheres, and finally the titanium oxide composite microspheres coated with chitosan are obtained.

[0010] Furthermore, the preparation method of the surface-modified boron nitride nanotube-coated nanosilver particles is as follows: by weight, 4 to 8 parts of silane coupling agent KH550 and 80 parts of chloroform are evenly mixed, and then 8 to 18 parts of boron nitride nanotube-coated nanosilver particles are added, magnetically stirred at room temperature for 4 to 9 hours, and then vacuum dried at room temperature to obtain surface-modified boron nitride nanotube-coated nanosilver particles.

[0011] Furthermore, the preparation method of the titanium oxide composite microspheres is as follows: after uniformly mixing 3 to 8 parts of zinc acetate dihydrate and 100 parts of anhydrous ethanol by weight, 5 to 10 parts of titanium oxide porous hollow microspheres are added, and magnetic stirring is performed for 10 to 20 minutes; then, the mixed solution is filtered, the titanium oxide porous hollow microspheres are collected, and vacuum dried at room temperature. After drying, the microspheres are placed in an air atmosphere and annealed at 150 to 180° C. for 30 to 60 minutes. Finally, after naturally cooling, the titanium oxide composite microspheres can be obtained.

[0012] Furthermore, the preparation method of the titanium oxide porous hollow microspheres is as follows: by weight, 10 to 20 parts of tetrabutyl titanate and 100 parts of anhydrous ethanol are mixed evenly, and then the evenly mixed solution is put into an autoclave and reacted at 220 to 250° C. for 3 to 5 hours, and then filtered to obtain a filter residue, which is then washed three times with anhydrous ethanol solution, each washing requires that the filter residue be completely submerged with anhydrous ethanol, and finally dried in an oven at 50 to 80° C. for 8 to 15 hours.

[0013] Furthermore, the titanium oxide composite microspheres are composed of titanium oxide porous hollow microspheres and divergent zinc oxide nanowires distributed on the surface thereof.

[0014] Furthermore, the average size of the titanium oxide composite microspheres is 60 to 95 nm.

[0015] The present invention designs titanium oxide composite microspheres coated with chitosan for multiple purposes: the titanium oxide composite microspheres cleverly integrate chitosan coating layers, and this design gives full play to the synergistic advantages of organic-inorganic composite materials in enhancing mechanical properties and antibacterial efficacy. Specifically, the inorganic component constructs a complex structure interwoven with porous titanium oxide hollow microspheres and radial zinc oxide nanowires, which significantly enhances the overall mechanical properties of the composite material by virtue of its excellent mechanical strength, toughness, and the unique bridging and winding effects of nanowires. In addition, titanium oxide and nanoscale zinc oxide jointly exhibit excellent antibacterial ability, and their porous structure and the wide distribution of nanowires greatly increase the specific surface area, providing abundant sites for antibacterial activity, thereby effectively improving the antibacterial efficiency. It is particularly worth mentioning that chitosan, as an organic component, is not simply mixed, but is carefully coated inside the porous titanium oxide microspheres. This innovative coating strategy not only avoids the potential risk of decreased mechanical properties of the oral denture base that may be caused by the direct addition of chitosan, but also cleverly utilizes the sustained-release properties of chitosan to achieve long-term maintenance of the antibacterial effect. This effectively avoids the problem of excessive local concentration and potential toxicity caused by the rapid release of drugs, and further improves the biosafety and application reliability of the composite material. In terms of antibacterial mechanism, chitosan, titanium oxide and zinc oxide show a significant synergistic effect: chitosan, with its inherent biocompatibility and antibacterial activity, continuously inhibits bacterial growth during the slow release process; at the same time, it can also synergize with titanium oxide and zinc oxide to jointly enhance the overall antibacterial efficacy of the composite material. Therefore, this design not only improves the mechanical properties of the composite material, but also achieves a long-lasting, efficient and safe antibacterial effect, bringing new application possibilities and broad development prospects to the field of oral denture bases.

[0016] Furthermore, the preparation method of the boron nitride nanotube-coated nanosilver particles is as follows: by weight, 3 to 6 parts of boron nitride nanotubes are placed in 30 to 45 parts of a 10% silver nitrate aqueous solution, and then stirred for 10 to 20 hours, and then the mixed solution is filtered and washed once with deionized water to remove the silver nitrate on the surface, and then it is placed in 40 to 60 parts of a 5% trisodium citrate solution, and then left for 15 to 25 hours to reduce the silver ions of the boron nitride nanotubes to nanosilver particles, and finally filtered, washed three times with deionized water, and finally vacuum dried to obtain the boron nitride nanotube-coated nanosilver particles.

[0017] Furthermore, the preparation method of the boron nitride nanotubes is as follows: 5 to 10 parts of lithium oxide and 2 to 5 parts of boron oxide are uniformly ball-milled to obtain nano-mixed particles, which are then placed in a tubular furnace in an ammonia atmosphere and heat-treated at 1000 to 1200° C. for 2 to 4 hours. After cooling, the particles are soaked in 30 to 50 parts of a 10% hydrochloric acid solution by mass for 3 to 6 hours, filtered, washed with deionized water for 3 times, and finally dried at 60 to 80° C. for 10 to 18 hours.

[0018] The present invention designs a surface-modified boron nitride nanotube-coated nanosilver particle composite material, and applies it to a light-cured acrylic resin-based denture base material, aiming to significantly improve the comprehensive performance of the denture base. By surface-modifying the boron nitride nanotubes and introducing the silane coupling agent KH550, the interfacial bonding strength between the nanotubes and the resin matrix can be enhanced, the mechanical properties of the composite material can be improved, and the dispersibility of the nanotubes can be improved to prevent them from agglomerating in the resin matrix, thereby ensuring the uniformity and stability of the composite material. In terms of mechanical properties, one-dimensional boron nitride nanotubes, as a reinforcing phase, can significantly improve the strength and toughness of the denture base by virtue of their excellent mechanical properties, such as high strength, high modulus and good toughness. The high aspect ratio and large specific surface area of ​​the nanotubes are conducive to the effective transmission and dispersion of stress, and the surface modification further enhances the interfacial bonding between the nanotubes and the resin matrix, maximizing the reinforcing and toughening effect of the nanotubes. In terms of antibacterial properties, nanosilver particles have excellent antibacterial activity. Encapsulating them in boron nitride nanotubes can achieve sustained-release antibacterial activity, prolong antibacterial time, prevent nanosilver particles from agglomerating, maintain a high specific surface area and antibacterial activity, significantly improve the antibacterial properties of denture bases, and reduce the risk of oral infection. In addition, the good biocompatibility of boron nitride nanotubes ensures the biosafety of the composite material, while surface modification can improve the hydrophilicity and wettability of the material, improve its compatibility with the oral mucosa, and reduce foreign body sensation and discomfort. It is worth noting that the surface-modified boron nitride nanotube-coated nanosilver particle composite material exhibits an excellent synergistic enhancement effect in the photocured acrylic resin-based denture base. Boron nitride nanotubes and nanosilver particles play a synergistic role in mechanical enhancement and antibacterial properties. Surface modification promotes the compatibility of nanomaterials with the resin matrix, forming a more uniform and stable composite structure, which significantly improves the performance of the denture base in many aspects, including mechanical properties, antibacterial properties and biocompatibility, providing patients with a more comfortable, durable and healthy denture restoration solution, and has broad application prospects.

[0019] It is worth noting that the surface-modified boron nitride nanotube-coated nanosilver particle composite material and the titanium oxide composite microsphere-coated chitosan of the present invention are both intended to improve the comprehensive performance of oral denture base materials, but they are different in design concepts and emphasis, and also show unique synergistic effects. The surface-modified boron nitride nanotube-coated nanosilver particle composite material focuses on utilizing the excellent properties of inorganic nanomaterials, enhancing the interface bonding between nanotubes and resin matrix through surface modification, and improving the mechanical properties and antibacterial effect of the composite material. Among them, boron nitride nanotubes, as a one-dimensional reinforcement phase, significantly improve the mechanical properties of the denture base with high strength, high modulus and good toughness. Nanosilver particles use their excellent antibacterial activity to achieve sustained release and antibacterial inhibition by coating in boron nitride nanotubes, prolonging the antibacterial time and preventing particle agglomeration. These two nanomaterials show synergistic effects in mechanical enhancement and antibacterial inhibition. At the same time, surface modification further promotes the compatibility of nanomaterials with resin matrix, forming a more uniform and stable composite structure. The titanium oxide composite microspheres coated with chitosan cleverly combine inorganic titanium oxide composite microspheres with organic chitosan, giving full play to the synergistic advantages of organic-inorganic composite materials. Among them, the titanium oxide composite microspheres are composed of porous titanium oxide hollow microspheres and radial zinc oxide nanowires. With their excellent mechanical strength, toughness, and the bridging and entanglement effect of nanowires, the mechanical properties of the composite material are significantly enhanced. At the same time, the porous structure and nanowire distribution of titanium oxide and zinc oxide provide abundant antibacterial sites, greatly improving the antibacterial efficiency. Chitosan, as an organic component, is carefully coated inside the titanium oxide porous microspheres, and its sustained release characteristics are used to achieve long-term antibacterial effect, and it has a synergistic effect with titanium oxide and zinc oxide, further enhancing the overall antibacterial efficacy of the composite material. In general, both composite materials are committed to improving the mechanical properties and antibacterial effects of denture bases, but with different focuses. The surface-modified boron nitride nanotubes coated with nanosilver particles composite material mainly utilizes the excellent properties of inorganic nanomaterials to enhance the comprehensive performance of the composite material through surface modification and synergistic effects. Titanium oxide composite microspheres coated with chitosan cleverly combine inorganic titanium oxide composite microspheres with organic chitosan, and use the unique advantages of organic-inorganic composite materials to achieve the purpose of improving mechanical properties and long-term antibacterial. The design concepts and focuses of these two composite materials are different, but both show significant synergistic effects, providing new ideas and broad development prospects for the modification and application of oral denture base materials.

[0020] The present invention adds polyetheretherketone (PEEK) material to the denture base, which mainly has the following purposes: Improving the strength and toughness of the denture base: Polyetheretherketone is a high-performance thermoplastic engineering plastic with excellent mechanical strength and toughness. Adding it to the traditional acrylic resin denture base can significantly improve the bending strength, impact resistance and fatigue resistance of the denture, and reduce the risk of the denture breaking or breaking during use. Improving the biocompatibility of the denture: Polyetheretherketone material has good biocompatibility and will not cause allergic reactions or inflammation when in contact with human tissues and body fluids. Using it to make a denture base can reduce the stimulation of the denture to the oral mucosa and improve the comfort and tolerance of the patient. Reducing the water absorption of the denture: Polyetheretherketone has excellent hydrophobicity and chemical stability, and has an extremely low water absorption rate. Adding polyetheretherketone can reduce the dimensional changes caused by water absorption of the denture base, improve the dimensional stability of the denture, and extend the service life of the denture. Simplify the denture processing technology: Polyetheretherketone materials can be prepared by injection molding, die-casting and other processes, with high production efficiency, and can realize the mass production of denture bases. At the same time, the thermoplasticity of polyetheretherketone also makes the repair and relining of dentures more convenient. Give dentures a beautiful appearance: Polyetheretherketone can achieve different coloring by adding pigments or dyes, and prepare denture bases with translucent effects and uniform colors to meet patients' needs for beautiful dentures. In summary, adding polyetheretherketone materials to denture bases can comprehensively improve the mechanical properties, biocompatibility and user experience of dentures, which is of great significance for improving patients' oral function and quality of life.

[0021] Furthermore, the photoinitiator is (2,4,6-trimethylbenzoyl)diphenylphosphine oxide or photoinitiator 907.

[0022] Furthermore, the dispersant is BYK-9076 or BYK-2152.

[0023] Furthermore, the defoaming agent is BYK-1790.

[0024] The present invention also provides a method for preparing a 3D printed high-strength oral denture base, comprising the following steps:

[0025] S1: Dispersing fillers: Ultrasonic dispersion of titanium oxide composite microspheres coated with chitosan, surface-modified boron nitride nanotubes coated with nanosilver particles, solvent and dispersant for 10 to 20 minutes, and then mechanically stirring for 40 to 90 minutes to obtain a uniformly dispersed filler mixed solution;

[0026] S2: preparing oral resin material base liquid: adding acrylic resin, polyetheretherketone, defoaming agent and photoinitiator to the uniformly dispersed filler mixed solution of S1, and continuing mechanical stirring for 60 to 120 minutes to obtain the oral resin material base liquid;

[0027] S3: Printing the denture base: Add the S2 oral resin material base liquid into the output pump of the DLP light-curing 3D printer, use computer-aided software to import the model file of the denture base, set the printing parameters, and print the denture base;

[0028] S4: Finishing treatment: Separate the solidified denture base from the mold, cool it to room temperature, and then subject the base surface to coarse grinding and fine grinding treatments in sequence.

[0029] (3) Beneficial technical effects

[0030] 1. The present invention innovatively combines titanium oxide composite microspheres with chitosan coatings to enhance mechanical properties and antibacterial efficacy. The porous titanium oxide microspheres and zinc oxide nanowires interwoven structure constructed by inorganic components significantly enhance the mechanical properties; their porous and nanowire properties improve the antibacterial efficiency. Chitosan is cleverly coated inside to avoid the decline of mechanical properties, and the sustained-release properties are used to maintain long-term antibacterial effects. At the same time, it synergizes with titanium oxide and zinc oxide to achieve efficient and safe antibacterial effects. This design shows great potential and application prospects in improving the performance of oral denture bases.

[0031] 2. The present invention also proposes a composite material of surface-modified boron nitride nanotubes coated with nanosilver particles, aiming to optimize the comprehensive performance of light-cured acrylic resin-based denture bases. The surface modification of boron nitride nanotubes by silane coupling agent KH550 not only strengthens the interface bonding between the nanotubes and the resin matrix, promotes the uniform dispersion of the nanotubes, but also improves the mechanical strength and toughness of the composite material. Boron nitride nanotubes, with their excellent mechanical properties and unique morphological characteristics, effectively transmit and disperse stress, significantly enhancing the mechanical properties of the denture base. At the same time, the coating of nanosilver particles achieves the sustained release and long-term effect of antibacterial properties, maintains high antibacterial activity, and effectively reduces the risk of oral infection. The composite material also exhibits good biocompatibility and surface wettability, improving the comfort of patients.

[0032] 3. In the present invention, surface-modified boron nitride nanotubes coated with nanosilver particles and titanium oxide composite microspheres coated with chitosan are both intended to improve the performance of oral denture bases, but the design concepts and focuses are different. The former focuses on the excellent performance of inorganic nanomaterials, enhances interfacial bonding through surface modification, and improves mechanical and antibacterial effects; boron nitride nanotubes strengthen mechanical properties, and nanosilver particles achieve sustained-release antibacterial effects. The latter combines inorganic titanium oxide composite microspheres with organic chitosan to give full play to the advantages of organic-inorganic composites; titanium oxide composite microspheres strengthen mechanics, and the porous structure improves antibacterial efficiency; chitosan coating achieves long-term antibacterial effects, and the synergistic effect of the three is significant. Although both have their own advantages, they both show synergistic effects, opening up new paths for the modification of denture base materials, and have broad prospects.

[0033] 4. The present invention introduces polyetheretherketone (PEEK) into the denture base, aiming to: enhance the strength and toughness of the denture, improve the bending resistance, impact resistance and fatigue resistance; improve biocompatibility, reduce oral irritation, and improve comfort; reduce water absorption, enhance dimensional stability, and extend service life; simplify the processing flow, support efficient mass production and convenient maintenance; give the denture an aesthetic appearance to meet personalized needs. In addition, specific photoinitiators (such as (2,4,6-trimethylbenzoyl) diphenylphosphine oxide or 907), dispersants (such as BYK-9076 or BYK-2152) and defoamers (such as BYK-1790) are also used to optimize material properties and processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscope morphology image of the titanium oxide porous hollow microspheres prepared in Example 1 of the present invention.

[0035] Figure 2 This is a scanning electron microscope morphology image of the titanium oxide composite microspheres prepared in Example 1 of the present invention.

[0036] Figure 3 This is a scanning electron microscope morphology image of the titanium oxide composite microspheres coated with chitosan prepared in Example 1 of the present invention.

[0037] Figure 4 This is the XRD diagram of the phase of the hollow microspheres prepared in Example 1 of the present invention.

[0038] Figure 5 This is the XRD diagram of the phase of the titanium oxide composite microstructure prepared in Example 1 of the present invention.

[0039] Figure 6 This is the phase XRD diagram of the titanium oxide composite microspheres coated with chitosan prepared in Example 1 of the present invention.

[0040] Figure 7 This is a scanning electron microscope morphology image of the surface-modified boron nitride nanotube-coated nanosilver particles prepared in Example 1 of the present invention.

[0041] Figure 8 This is a transmission electron microscope morphology image of the surface-modified boron nitride nanotube-coated nanosilver particles prepared in Example 1 of the present invention.

[0042] Fig. 9 This is a physical picture of the 3D printed denture base according to Example 1 of the present invention. DETAILED DESCRIPTION

[0043] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0044] In the absence of specific conditions, the operations in the examples are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. Parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0045] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies

[0046]

[0047]

[0048] Example 1

[0049] A 3D printed high-strength oral denture base is prepared from the following components by weight: 5 parts of titanium oxide composite microspheres coated with chitosan, 4 parts of surface-modified boron nitride nanotubes coated with nanosilver particles, 80 parts of acrylic resin, 4 parts of polyetheretherketone, 20 parts of anhydrous ethanol, 1 part of BYK-1790, 2 parts of BYK-9076, or 2 parts of photoinitiator 907.

[0050] The preparation method of titanium oxide composite microspheres coated with chitosan is as follows: by weight, 3 parts of chitosan are dissolved in 20 parts of 2% acetic acid aqueous solution, stirred for 15 minutes, then 10 parts of titanium oxide composite microspheres are added, ultrasonically treated for 10 minutes, and then vacuum impregnated for 15 minutes, and finally vacuum dried at room temperature for 10 hours, and this vacuum impregnation-vacuum drying cycle is repeated 3 times. After all cycles are completed, the product is washed with deionized water. During the washing process, it is necessary to ensure that the deionized water completely submerges the titanium oxide composite microspheres, and finally the titanium oxide composite microspheres coated with chitosan are obtained.

[0051] The preparation method of surface-modified boron nitride nanotube-coated silver nanoparticles is as follows: by weight, 4 parts of silane coupling agent KH550 and 80 parts of chloroform are evenly mixed, and then 8 parts of boron nitride nanotube-coated silver nanoparticles are added, magnetically stirred at room temperature for 4 hours, and then vacuum dried at room temperature to obtain surface-modified boron nitride nanotube-coated silver nanoparticles.

[0052] The preparation method of titanium oxide composite microspheres in this embodiment is as follows: after evenly mixing 3 parts of zinc acetate dihydrate and 100 parts of anhydrous ethanol by weight, 5 parts of titanium oxide porous hollow microspheres are added, and magnetic stirring is performed for 10 minutes; then, the mixed solution is filtered, the titanium oxide porous hollow microspheres are collected, and vacuum dried at room temperature. After drying, the microspheres are placed in an air atmosphere and annealed at 150° C. for 30 minutes. Finally, after naturally cooling, titanium oxide composite microspheres can be obtained.

[0053] The preparation method of the porous hollow titanium oxide microspheres in this embodiment is as follows: 10 parts of tetrabutyl titanate and 100 parts of anhydrous ethanol are mixed evenly by weight, and then the evenly mixed solution is put into an autoclave and reacted at 220°C for 3 hours, and then filtered to obtain a filter residue, and then washed three times with anhydrous ethanol solution, each washing needs to completely submerge the filter residue with anhydrous ethanol, and finally dried in an oven at 50°C for 8 hours.

[0054] The titanium oxide composite microspheres of this embodiment are composed of titanium oxide porous hollow microspheres and divergent zinc oxide nanowires distributed on the surface thereof.

[0055] The average size of the titanium oxide composite microspheres in this embodiment is 60 nm.

[0056] The preparation method of the boron nitride nanotube-coated nanosilver particles of the present embodiment is as follows: by weight, 3 parts of boron nitride nanotubes are put into 30 parts of a 10% silver nitrate aqueous solution, and then stirred for 10 hours, and then the mixed solution is filtered and washed once with deionized water to remove the silver nitrate on the surface, and then it is put into 40 parts of a 5% trisodium citrate solution by mass, and then left for 15 hours to reduce the silver ions of the boron nitride nanotubes into nanosilver particles, and finally filtered, washed three times with deionized water, and finally vacuum dried to obtain the boron nitride nanotube-coated nanosilver particles.

[0057] The preparation method of boron nitride nanotubes in this embodiment is as follows: 5 parts of lithium oxide and 2 parts of boron oxide are uniformly ball-milled to obtain nano-mixed particles, which are then placed in a tubular furnace in an ammonia atmosphere and heat-treated at 1000° C. for 2 hours. After cooling, the particles are soaked in 30 parts of a 10% by mass hydrochloric acid solution for 3 hours, then filtered and washed with deionized water for 3 times, and finally dried at 60° C. for 10 hours.

[0058] This embodiment also provides a method for preparing a 3D printed high-strength oral denture base, comprising the following steps:

[0059] S1: Dispersing fillers: Ultrasonic dispersion of titanium oxide composite microspheres coated with chitosan, surface-modified boron nitride nanotubes coated with nanosilver particles, solvent and dispersant for 10 min, and then mechanically stirred for 40 min to obtain a uniformly dispersed filler mixed solution;

[0060] S2: Preparation of oral resin material base liquid: Continue to add acrylic resin, polyetheretherketone, defoaming agent and photoinitiator to the uniformly dispersed filler mixed solution of S1, and continue mechanical stirring for 60 minutes to obtain the oral resin material base liquid.

[0061] S3: Printing and molding denture base: Add S2 oral resin material base liquid into the output pump of DLP light-curing 3D printer, use computer-aided software to import the model file of the molding denture base, set the printing parameters, and print the denture base.

[0062] S4: Finishing treatment: Separate the solidified denture base from the mold, cool it to room temperature, and then subject the base surface to coarse grinding and fine grinding treatments in sequence.

[0063] Figure 1 This is a scanning electron microscope morphology image of the porous hollow titanium oxide microspheres prepared in Example 1 of the present invention. It can be clearly observed from the image that the titanium oxide microspheres have porous and hollow structural characteristics, proving that Example 1 successfully prepared titanium oxide microspheres with porous hollow structures.

[0064] Figure 2 This is a scanning electron microscope morphology image of the titanium oxide composite microspheres prepared in Example 1 of the present invention. The image clearly shows that a large number of nanowire structures grow on the surface of the titanium oxide composite microspheres, while the porous hollow morphology is still maintained inside, proving that nanowire morphology has been successfully grown on the surface of the porous hollow titanium oxide microspheres.

[0065] Figure 3 This is a scanning electron microscope morphology of the titanium oxide composite microspheres coated with chitosan prepared in Example 1 of the present invention. It can be clearly seen that chitosan is successfully coated inside the titanium oxide composite microspheres, proving that the titanium oxide composite microspheres prepared in Example 1 are successfully coated with chitosan.

[0066] Figure 4 Phase XRD diagrams of hollow microspheres, titanium oxide composite microspheres, and titanium oxide composite microspheres coated with chitosan prepared in Example 1 of the present invention.

[0067] Figure 5 This is the phase XRD diagram of the titanium oxide composite microspheres prepared in Example 1 of the present invention. In the diagram, the diffraction peaks of the titanium oxide composite microspheres simultaneously show the characteristic peaks of titanium dioxide and zinc oxide.

[0068] Figure 6 The XRD diagram of the phase of titanium oxide composite microspheres coated with chitosan prepared in Example 1 of the present invention has not only diffraction peaks of titanium dioxide and zinc oxide, but also superimposed diffraction peaks of chitosan, proving the phase composition of titanium dioxide / zinc oxide / chitosan.

[0069] Figure 7 This is a scanning electron microscope morphology of the surface-modified boron nitride nanotubes coated with nanosilver particles prepared in Example 1 of the present invention. As can be seen from the figure, the prepared sample exhibits obvious nanowire-like morphology characteristics, proving that Example 1 successfully prepared surface-modified boron nitride nanotubes with nanowire morphology.

[0070] Figure 8 This is a transmission electron microscope morphology of the surface-modified boron nitride nanotubes coated with nanosilver particles prepared in Example 1 of the present invention. The figure clearly shows that the nanowire-shaped boron nitride is coated with nanoparticles, proving that the nanosilver particles are successfully coated inside the surface-modified boron nitride nanotubes.

[0071] Fig. 9 This is a real picture of the denture base printed by 3D printing in Example 1 of the present invention. The figure shows the finished denture base obtained by 3D printing technology using the oral resin material prepared in Example 1, which proves that the material prepared by the present invention can be well applied to 3D printing to achieve rapid prototyping of the denture base.

[0072] Example 2

[0073] A 3D printed high-strength oral denture base is prepared from the following components by weight: 7 parts of titanium oxide composite microspheres coated with chitosan, 6 parts of surface-modified boron nitride nanotubes coated with nanosilver particles, 92 parts of acrylic resin, 6 parts of polyetheretherketone, 24 parts of anhydrous ethanol, 1.6 parts of BYK-1790, 3 parts of BYK-2152, and 3 parts of photoinitiator 907.

[0074] The preparation method of titanium oxide composite microspheres coated with chitosan is as follows: by weight, 5 parts of chitosan are dissolved in 24 parts of 2% acetic acid aqueous solution, stirred for 21 minutes, then 14 parts of titanium oxide composite microspheres are added, ultrasonically treated for 14 minutes, and then vacuum impregnated for 21 minutes, and finally vacuum dried at room temperature for 13 hours, and this vacuum impregnation-vacuum drying cycle is repeated 3 times. After all cycles are completed, the product is washed with deionized water. During the washing process, it is necessary to ensure that the deionized water completely submerges the titanium oxide composite microspheres, and finally the titanium oxide composite microspheres coated with chitosan are obtained.

[0075] The preparation method of surface-modified boron nitride nanotube-coated silver nanoparticles is as follows: by weight, 6 parts of silane coupling agent KH550 and 80 parts of chloroform are evenly mixed, and then 12 parts of boron nitride nanotube-coated silver nanoparticles are added, magnetic stirring is performed at room temperature for 6 hours, and then vacuum drying is performed at room temperature to obtain surface-modified boron nitride nanotube-coated silver nanoparticles.

[0076] The preparation method of titanium oxide composite microspheres in this embodiment is as follows: after evenly mixing 5 parts of zinc acetate dihydrate and 100 parts of anhydrous ethanol by weight, 7 parts of titanium oxide porous hollow microspheres are added, and magnetic stirring is performed for 14 minutes; then, the mixed solution is filtered, the titanium oxide porous hollow microspheres are collected, and vacuum dried at room temperature. After drying, the microspheres are placed in an air atmosphere and annealed at 162° C. for 42 minutes. Finally, after naturally cooling, titanium oxide composite microspheres can be obtained.

[0077] The preparation method of the porous hollow microspheres of titanium oxide in this embodiment is as follows: 14 parts of tetrabutyl titanate and 100 parts of anhydrous ethanol are mixed evenly by weight, and then the evenly mixed solution is put into an autoclave and reacted at 232°C for 4 hours, and then filtered to obtain a filter residue, and then washed three times with anhydrous ethanol solution, each washing requires that the filter residue be completely submerged with anhydrous ethanol, and finally dried in an oven at 62°C for 11 hours.

[0078] The titanium oxide composite microspheres of this embodiment are composed of titanium oxide porous hollow microspheres and divergent zinc oxide nanowires distributed on the surface thereof.

[0079] The average size of the titanium oxide composite microspheres in this example is 74.5 nm.

[0080] The preparation method of the boron nitride nanotube-coated nanosilver particles in this embodiment is as follows: by weight, 4 parts of boron nitride nanotubes are placed in 36 parts of a 10% silver nitrate aqueous solution, and then stirred for 14 hours. The mixed solution is then filtered and washed once with deionized water to remove the silver nitrate on the surface. Then, the mixed solution is placed in 48 parts of a 5% trisodium citrate solution and left for another 19 hours to reduce the silver ions of the boron nitride nanotubes to nanosilver particles. Finally, the mixture is filtered and washed three times with deionized water. Finally, the mixture is vacuum dried to obtain the boron nitride nanotube-coated nanosilver particles.

[0081] The preparation method of boron nitride nanotubes in this embodiment is as follows: 7 parts of lithium oxide and 3 parts of boron oxide are uniformly ball-milled to obtain nano-mixed particles, which are then placed in a tubular furnace in an ammonia atmosphere and heat-treated at 1084°C for 3 hours. After cooling, the particles are soaked in 38 parts of a 10% hydrochloric acid solution by mass for 4 hours, filtered, washed with deionized water for 3 times, and finally dried at 68°C for 13 hours.

[0082] This embodiment also provides a method for preparing a 3D printed high-strength oral denture base, comprising the following steps:

[0083] S1: Dispersed filler: Titanium oxide composite microspheres coated with chitosan, surface-modified boron nitride nanotubes coated with nanosilver particles, solvent and dispersant were first ultrasonically dispersed for 14 minutes, and then mechanically stirred for 60 minutes to obtain a uniformly dispersed filler mixed solution;

[0084] S2: preparing oral resin material base liquid: continuing to add acrylic resin, polyetheretherketone, defoaming agent and photoinitiator to the uniformly dispersed filler mixed solution of S1, and continuing mechanical stirring for 84 minutes to obtain the oral resin material base liquid.

[0085] S3: Printing and forming denture base: Add S2 oral resin material base liquid into the output pump of DLP light-curing 3D printer, use computer-aided software to import the model file of the denture base, set the printing parameters, and print the denture base.

[0086] S4: Finishing treatment: Separate the solidified denture base from the mold, cool it to room temperature, and then subject the base surface to coarse grinding and fine grinding treatments in sequence.

[0087] Example 3

[0088] A 3D printed high-strength oral denture base is prepared from the following components by weight: 7 parts of titanium oxide composite microspheres coated with chitosan, 7 parts of surface-modified boron nitride nanotubes coated with nanosilver particles, 98 parts of acrylic resin, 7 parts of polyetheretherketone, 26 parts of anhydrous ethanol, 2 parts of BYK-1790, 4 parts of BYK-9076, and 3 parts of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide.

[0089] The preparation method of titanium oxide composite microspheres coated with chitosan is as follows: by weight, 6 parts of chitosan are dissolved in 26 parts of 2% acetic acid aqueous solution, stirred for 23 minutes, then 16 parts of titanium oxide composite microspheres are added, ultrasonically treated for 16 minutes, and then vacuum impregnated for 23 minutes, and finally vacuum dried at room temperature for 15 hours, and this vacuum impregnation-vacuum drying cycle is repeated 3 times. After all cycles are completed, the product is washed with deionized water. During the washing process, it is necessary to ensure that the deionized water completely submerges the titanium oxide composite microspheres, and finally the titanium oxide composite microspheres coated with chitosan are obtained.

[0090] The preparation method of surface-modified boron nitride nanotube-coated silver nanoparticles is as follows: by weight, 6 parts of silane coupling agent KH550 and 80 parts of chloroform are evenly mixed, and then 14 parts of boron nitride nanotube-coated silver nanoparticles are added, magnetic stirring is performed at room temperature for 7 hours, and then vacuum drying is performed at room temperature to obtain surface-modified boron nitride nanotube-coated silver nanoparticles.

[0091] The preparation method of titanium oxide composite microspheres in this embodiment is as follows: after uniformly mixing 6 parts of zinc acetate dihydrate and 100 parts of anhydrous ethanol by weight, 8 parts of titanium oxide porous hollow microspheres are added, and magnetic stirring is performed for 16 minutes; then, the mixed solution is filtered, the titanium oxide porous hollow microspheres are collected, and vacuum dried at room temperature. After drying, the microspheres are placed in an air atmosphere and annealed at 168° C. for 48 minutes. Finally, after naturally cooling, titanium oxide composite microspheres can be obtained.

[0092] The preparation method of the titanium oxide porous hollow microspheres in this embodiment is as follows: 16 parts of tetrabutyl titanate and 100 parts of anhydrous ethanol are mixed evenly by weight, and then the evenly mixed solution is put into an autoclave and reacted at 238°C for 4 hours, and then filtered to obtain a filter residue, and then washed three times with anhydrous ethanol solution, each washing requires that the filter residue be completely submerged with anhydrous ethanol, and finally dried in an oven at 68°C for 12.4 hours.

[0093] The titanium oxide composite microspheres of this embodiment are composed of titanium oxide porous hollow microspheres and divergent zinc oxide nanowires distributed on the surface thereof.

[0094] The average size of the titanium oxide composite microspheres in this example is 81 nm.

[0095] The preparation method of the boron nitride nanotube-coated nanosilver particles in this embodiment is as follows: by weight, 5 parts of boron nitride nanotubes are placed in 39 parts of a 10% silver nitrate aqueous solution, and then stirred for 16 hours. The mixed solution is then filtered and washed once with deionized water to remove the silver nitrate on the surface. Then, the mixed solution is placed in 52 parts of a 5% trisodium citrate solution and left for 21 hours to reduce the silver ions of the boron nitride nanotubes to nanosilver particles. Finally, the mixture is filtered and washed three times with deionized water. Finally, the mixture is vacuum dried to obtain the boron nitride nanotube-coated nanosilver particles.

[0096] The preparation method of boron nitride nanotubes in this embodiment is as follows: 8 parts of lithium oxide and 4 parts of boron oxide are uniformly ball-milled to obtain nano-mixed particles, which are then placed in a tubular furnace in an ammonia atmosphere and heat-treated at 1120° C. for 3.2 hours. After cooling, the particles are soaked in 42 parts of a 10% hydrochloric acid solution by mass for 5 hours, filtered, washed with deionized water for 3 times, and finally dried at 72° C. for 15 hours.

[0097] This embodiment also provides a method for preparing a 3D printed high-strength oral denture base, comprising the following steps:

[0098] S1: Dispersed filler: Titanium oxide composite microspheres coated with chitosan, surface-modified boron nitride nanotubes coated with nanosilver particles, solvent and dispersant were first ultrasonically dispersed for 16 minutes, and then mechanically stirred for 70 minutes to obtain a uniformly dispersed filler mixed solution;

[0099] S2: preparing oral resin material base liquid: continuing to add acrylic resin, polyetheretherketone, defoaming agent and photoinitiator to the uniformly dispersed filler mixed solution of S1, and continuing mechanical stirring for 96 minutes to obtain the oral resin material base liquid.

[0100] S3: Printing and forming denture base: Add S2 oral resin material base liquid into the output pump of DLP light-curing 3D printer, use computer-aided software to import the model file of the denture base, set the printing parameters, and print the denture base.

[0101] S4: Finishing treatment: Separate the solidified denture base from the mold, cool it to room temperature, and then subject the base surface to coarse grinding and fine grinding treatments in sequence.

[0102] Example 4

[0103] A 3D printed high-strength oral denture base is prepared from the following components by weight: 10 parts of titanium oxide composite microspheres coated with chitosan, 9 parts of surface-modified boron nitride nanotubes coated with nanosilver particles, 110 parts of acrylic resin, 10 parts of polyetheretherketone, 30 parts of anhydrous ethanol, 3 parts of BYK-1790, 25 parts of BYK-215, and 4 parts of photoinitiator 907.

[0104] The preparation method of titanium oxide composite microspheres coated with chitosan is as follows: by weight, 8 parts of chitosan are dissolved in 30 parts of 2% acetic acid aqueous solution, stirred for 30 minutes, then 20 parts of titanium oxide composite microspheres are added, ultrasonically treated for 20 minutes, and then vacuum impregnated for 30 minutes, and finally vacuum dried at room temperature for 18 hours, and this vacuum impregnation-vacuum drying cycle is repeated 3 times. After all cycles are completed, the product is washed with deionized water. During the washing process, it is necessary to ensure that the deionized water completely submerges the titanium oxide composite microspheres, and finally the titanium oxide composite microspheres coated with chitosan are obtained.

[0105] The preparation method of surface-modified boron nitride nanotube-coated silver nanoparticles is as follows: by weight, 8 parts of silane coupling agent KH550 and 80 parts of chloroform are evenly mixed, and then 18 parts of boron nitride nanotube-coated silver nanoparticles are added, magnetic stirring is performed at room temperature for 9 hours, and then vacuum drying is performed at room temperature to obtain surface-modified boron nitride nanotube-coated silver nanoparticles.

[0106] The preparation method of titanium oxide composite microspheres in this embodiment is as follows: after uniformly mixing 8 parts of zinc acetate dihydrate and 100 parts of anhydrous ethanol by weight, 10 parts of titanium oxide porous hollow microspheres are added, and magnetic stirring is performed for 20 minutes; then, the mixed solution is filtered, the titanium oxide porous hollow microspheres are collected, and vacuum dried at room temperature. After drying, the microspheres are placed in an air atmosphere and annealed at 180° C. for 60 minutes. Finally, after naturally cooling, titanium oxide composite microspheres can be obtained.

[0107] The preparation method of the porous hollow microspheres of titanium oxide in this embodiment is as follows: 20 parts of tetrabutyl titanate and 100 parts of anhydrous ethanol are mixed evenly by weight, and then the evenly mixed solution is put into an autoclave and reacted at 250°C for 5 hours, and then filtered to obtain a filter residue, which is then washed three times with anhydrous ethanol solution, each washing requiring the filter residue to be completely submerged with anhydrous ethanol, and finally dried in an oven at 80°C for 15 hours.

[0108] The titanium oxide composite microspheres of this embodiment are composed of titanium oxide porous hollow microspheres and divergent zinc oxide nanowires distributed on the surface thereof.

[0109] The average size of the titanium oxide composite microspheres in this example is 95 nm.

[0110] The preparation method of the boron nitride nanotube-coated nanosilver particles in this embodiment is as follows: by weight, 6 parts of boron nitride nanotubes are placed in 45 parts of a 10% silver nitrate aqueous solution, and then stirred for 20 hours. The mixed solution is then filtered and washed once with deionized water to remove the silver nitrate on the surface. Then, the mixed solution is placed in 60 parts of a 5% trisodium citrate solution and left for another 25 hours to reduce the silver ions of the boron nitride nanotubes to nanosilver particles. Finally, the mixture is filtered and washed three times with deionized water. Finally, the mixture is vacuum dried to obtain the boron nitride nanotube-coated nanosilver particles.

[0111] The preparation method of boron nitride nanotubes in this embodiment is as follows: 10 parts of lithium oxide and 5 parts of boron oxide are uniformly ball-milled to obtain nano-mixed particles, which are then placed in a tubular furnace in an ammonia atmosphere and heat-treated at 1200°C for 4 hours. After cooling, the particles are soaked in 50 parts of a 10% hydrochloric acid solution by mass for 6 hours, filtered, washed with deionized water for 3 times, and finally dried at 80°C for 18 hours.

[0112] This embodiment also provides a method for preparing a 3D printed high-strength oral denture base, comprising the following steps:

[0113] S1: Dispersing fillers: Titanium oxide composite microspheres coated with chitosan, surface-modified boron nitride nanotubes coated with nanosilver particles, solvents and dispersants were first ultrasonically dispersed for 20 minutes, and then mechanically stirred for 90 minutes to obtain a uniformly dispersed filler mixed solution;

[0114] S2: preparing oral resin material base liquid: continuing to add acrylic resin, polyetheretherketone, defoaming agent and photoinitiator to the uniformly dispersed filler mixed solution of S1, and continuing mechanical stirring for 120 minutes to obtain the oral resin material base liquid.

[0115] S3: Printing and forming denture base: Add S2 oral resin material base liquid into the output pump of DLP light-curing 3D printer, use computer-aided software to import the model file of the denture base, set the printing parameters, and print the denture base.

[0116] S4: Finishing treatment: Separate the solidified denture base from the mold, cool it to room temperature, and then subject the base surface to coarse grinding and fine grinding treatments in sequence.

[0117] Example 5

[0118] It is basically the same as Example 1, except that the proportion of chitosan coated with titanium oxide composite microspheres in preparing the denture base is 7 parts.

[0119] Comparative Example 1

[0120] It is basically the same as Example 1, except that the titanium oxide composite microspheres used to prepare the denture base are not coated with chitosan.

[0121] Comparative Example 2

[0122] It is basically the same as Example 1, except that the denture base is prepared by using titanium oxide porous hollow microspheres coated with chitosan, so the surface of the titanium oxide porous hollow microspheres does not contain zinc oxide nanowires.

[0123] Comparative Example 3

[0124] It is basically the same as Example 1, except that the titanium oxide composite microspheres and chitosan are added separately to prepare the denture base, so the chitosan is not coated with the titanium oxide composite microspheres.

[0125] Comparative Example 4

[0126] It is basically the same as Example 1, except that the boron nitride nanotube-coated nanosilver particles in the preparation of the denture base are not subjected to surface modification treatment.

[0127] Comparative Example 5

[0128] It is basically the same as Example 1, except that the boron nitride nanotubes for preparing the surface modification of the denture base are not coated with nano-silver particles.

[0129] Performance Testing

[0130] Mechanical properties: To evaluate the mechanical properties of 3D printed denture bases, the printed denture base samples were processed into standard impact test specimens with dimensions of 64 mm × 10 mm × 3.3 mm in accordance with the requirements of the pharmaceutical industry standard of the People's Republic of China "YY 0270.1-2011 Dental base polymers Part 1: Denture bases". Six parallel specimens were prepared for each printing material to ensure the reliability of the test results. The specimens were subjected to a three-point bending test using a universal testing machine (model, manufacturer, country). The test process is as follows: The specimen was placed on two support rollers with a distance of 50 mm between the support rollers. A load was applied to the center of the specimen at a speed of 5 mm / min through a load-applying indenter until the specimen broke. The maximum load at which the specimen broke was recorded, and the bending strength and elastic modulus of the specimen were calculated according to the formula.

[0131] Antibacterial property: To evaluate the antibacterial properties of 3D printed denture base materials, this study used the optical density method (OD) to measure the concentration of Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) attached to the surface of the material. 7 CFU / mL of bacterial solution, and determine its initial OD value at 450nm. Then, dilute the bacterial solution 10, 50, 100 and 1000 times, and determine the OD values ​​at different dilutions. Use linear regression method to draw a standard curve of OD value and colony concentration, and calculate the correlation coefficient R. Soak the sterilized denture base samples in the bacterial solution and culture at 37℃ for 24 and 48h. Take out the samples and disperse the attached bacteria into physiological saline by ultrasonic oscillation. Determine the OD value of the bacterial suspension at 450nm, calculate the bacterial concentration using the standard curve, and calculate the antibacterial rate of the material.

[0132] Biocompatibility: The CCK-8 method was used to evaluate the cytotoxicity of the composite material to test its biocompatibility. The tooth base material was processed according to ISO 10993-12:200 standard, and the CCK-8 method was used to evaluate the cytotoxicity and biocompatibility of the tooth base material. The extract was collected after soaking in α-MEM culture medium. L929 cells were cultured in 96-well plates, and CCK-8 reagent was added at different time points to determine cell proliferation. The cell proliferation curve was analyzed by OD value, the cell survival rate was tested, and the cytotoxicity and biocompatibility of the material were evaluated.

[0133] The properties of the denture base materials of Examples 1 to 5 and Comparative Examples 1 to 5 are summarized in Table 2.

[0134] Table 2 Performance of denture base materials of Examples 1 to 5 and Comparative Examples 1 to 5

[0135]

[0136]

[0137] The main difference between Comparative Example 1 and Example 1 is whether the titanium oxide composite microspheres are coated with chitosan. It can be seen from Table 2 that the titanium oxide composite microspheres coated with chitosan can significantly improve the antibacterial performance of the tooth base, because chitosan has an inhibitory effect on a variety of bacteria, including common pathogens such as Escherichia coli and Staphylococcus aureus. This broad-spectrum antibacterial property helps to improve the hygiene of the tooth base and reduce the growth of oral bacteria, especially the coating of chitosan can exert a long-term antibacterial rate.

[0138] The main difference between Comparative Example 2 and Example 1 is whether the titanium oxide composite microspheres contain zinc oxide nanowires. Table 2 shows that the outer layer of the titanium oxide composite microspheres contains zinc oxide nanowires, which can significantly improve the mechanical properties of the tooth base. At the same time, the zinc oxide nanowires also have certain antibacterial properties.

[0139] The main difference between Comparative Example 3 and Example 1 is that the coating is chitosan and titanium oxide composite microspheres are added separately, so there is no coating relationship between the two. It can be seen from Table 2 that the lack of coating relationship between chitosan and titanium oxide composite microspheres leads to a decrease in the mechanical properties of the denture base. The most important thing is that there is a coating relationship between chitosan and titanium oxide composite microspheres, which allows chitosan to be slowly released, so the coating relationship can exert a long-lasting antibacterial effect. Therefore, the coating relationship between the two has a synergistic improvement in both mechanical and antibacterial effects.

[0140] The main difference between Comparative Example 4 and Example 1 is whether the boron nitride nanotube-coated silver particles are surface modified. From Table 2, it can be seen that the surface-treated boron nitride nanotube-coated silver particles can significantly improve the mechanical properties of the denture base. This is because the surface treatment can increase the interface bonding strength between the boron nitride nanotubes and the matrix, thereby increasing the mechanical properties of the denture base.

[0141] The main difference between Comparative Example 5 and Example 1 is whether the surface-modified boron nitride nanotubes are coated with nanosilver particles. It can be seen from Table 2 that the presence of nanosilver particles can significantly improve the antibacterial ability of the denture base.

[0142] In summary, the present invention integrates titanium oxide composite microspheres and chitosan coating layers, and utilizes porous microspheres and zinc oxide nanowires to enhance mechanical and antibacterial properties. The chitosan coating maintains long-term antibacterial properties without damaging mechanical properties, synergistically improving antibacterial efficiency, and has significant potential for improving the performance of oral denture bases. In addition, the composite material of surface-modified boron nitride nanotubes coated with nanosilver particles uses silane coupling agent KH550 to enhance the bonding between the nanotubes and the resin matrix, thereby improving mechanical properties and toughness. Boron nitride nanotubes enhance stress transfer and dispersion, while nanosilver particles achieve long-term antibacterial properties while maintaining good biocompatibility and surface wettability, optimizing the overall performance of denture bases, reducing the risk of infection, and improving comfort in use.

[0143] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A 3D printed high-strength oral denture base, characterized in that: The invention is prepared from the following components by weight: 5-10 parts of titanium oxide composite microspheres coated with chitosan, 4-9 parts of surface-modified boron nitride nanotubes coated with nano silver particles, 80-110 parts of acrylic resin, 4-10 parts of polyetheretherketone, 20-30 parts of anhydrous ethanol, 1-3 parts of defoaming agent, 2-5 parts of dispersant, and 2-4 parts of photoinitiator; The preparation method of the titanium oxide composite microsphere-coated chitosan is as follows: by weight, 3 to 8 parts of chitosan are dissolved in 20 to 30 parts of 2% acetic acid aqueous solution, stirred for 15 to 30 minutes, then 10 to 20 parts of titanium oxide composite microspheres are added, ultrasonic treatment is performed for 10 to 20 minutes, and then vacuum impregnation is performed for 15 to 30 minutes, and finally vacuum drying is performed at room temperature for 10 to 18 hours, and the vacuum impregnation-vacuum drying cycle is repeated 3 times. After all cycles are completed, the product is washed with deionized water. During the washing process, it is necessary to ensure that the deionized water completely submerges the titanium oxide composite microspheres, and finally the titanium oxide composite microsphere-coated chitosan is obtained; The preparation method of the surface-modified boron nitride nanotube-coated nanosilver particles is as follows: by weight, 4 to 8 parts of silane coupling agent KH550 and 80 parts of chloroform are evenly mixed, then 8 to 18 parts of boron nitride nanotube-coated nanosilver particles are added, magnetic stirring is performed at room temperature for 4 to 9 hours, and then vacuum drying is performed at room temperature to obtain the surface-modified boron nitride nanotube-coated nanosilver particles; The preparation method of the titanium oxide composite microspheres is as follows: after mixing 3 to 8 parts of zinc acetate dihydrate and 100 parts of anhydrous ethanol in parts by weight, 5 to 10 parts of titanium oxide porous hollow microspheres are added, and magnetic stirring is performed for 10 to 20 minutes; then, the mixed solution is filtered, the titanium oxide porous hollow microspheres are collected, and vacuum dried at room temperature. After drying, the microspheres are placed in an air atmosphere and annealed at 150 to 180° C. for 30 to 60 minutes. Finally, after cooling naturally, titanium oxide composite microspheres can be obtained; The preparation method of the titanium oxide porous hollow microspheres is as follows: by weight, 10 to 20 parts of tetrabutyl titanate and 100 parts of anhydrous ethanol are mixed evenly, and then the mixed solution is put into an autoclave and reacted at 220 to 250° C. for 3 to 5 hours, and then filtered to obtain a filter residue, and then washed it three times with anhydrous ethanol solution, each washing needs to be completely submerged in anhydrous ethanol, and finally dried in an oven at 50 to 80° C. for 8 to 15 hours; The preparation method of the boron nitride nanotube-coated nanosilver particles is as follows: by weight, 3 to 6 parts of boron nitride nanotubes are put into 30 to 45 parts of a 10% silver nitrate aqueous solution, and then stirred for 10 to 20 hours, and then the mixed solution is filtered, washed once with deionized water to remove the silver nitrate on the surface, and then put into 40 to 60 parts of a 5% trisodium citrate solution, and then left for 15 to 25 hours to reduce the silver ions of the boron nitride nanotubes to nanosilver particles, filtered, washed three times with deionized water, and finally vacuum dried to obtain the boron nitride nanotube-coated nanosilver particles; The photoinitiator is (2,4,6-trimethylbenzoyl) diphenylphosphine oxide or photoinitiator 907; The dispersant is BYK-9076 or BYK-2152; The defoamer is BYK-1790; The preparation method of the boron nitride nanotubes is as follows: 5-10 parts of lithium oxide and 2-5 parts of boron oxide are uniformly ball-milled to obtain nano-mixed particles, which are then placed in a tubular furnace in an ammonia atmosphere for heat treatment at 1000-1200° C. for 2-4 hours, and after cooling, are soaked in 30-50 parts of a 10% by mass hydrochloric acid solution for 3-6 hours, and then filtered and washed with deionized water for 3 times, and finally dried at 60-80° C. for 10-18 hours.

2. A 3D printed high-strength oral denture base as claimed in claim 1, characterized in that: The titanium oxide composite microspheres are composed of titanium oxide porous hollow microspheres and divergent zinc oxide nanowires distributed on the surface of the microspheres.

3. A 3D printed high-strength oral denture base as claimed in claim 1, characterized in that: The average size of the titanium oxide composite microspheres is 60-95 nm.

4. A method for preparing a 3D printed high-strength oral denture base according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Dispersing fillers: firstly ultrasonically disperse the titanium oxide composite microspheres coated with chitosan, the surface-modified boron nitride nanotubes coated with nanosilver particles, the solvent anhydrous ethanol and the dispersant for 10 to 20 minutes, and then mechanically stir for 40 to 90 minutes to obtain a uniformly dispersed filler mixed solution; S2: preparing oral resin material base liquid: adding acrylic resin, polyetheretherketone, defoaming agent and photoinitiator to the uniformly dispersed filler mixed solution of S1, and continuing mechanical stirring for 60 to 120 minutes to obtain the oral resin material base liquid; S3: Printing the denture base: Add the S2 oral resin material base liquid into the output pump of the DLP light-curing 3D printer, use computer-aided software to import the model file of the denture base, set the printing parameters, and print the denture base; S4: Finishing treatment: The solidified denture base is separated from the mold, cooled to room temperature, and the surface of the base is subjected to coarse grinding and fine grinding in sequence.

Citation Information

Patent Citations

  • Medical beauty antibacterial denture base material and preparation method thereof

    CN111789771A

  • Reinforced toughness type antibacterial denture base and preparation method thereof

    CN113181061A

  • Long-acting antibacterial resin compound denture base and preparation method thereof

    CN106511101A

  • Antibacterial oral denture base and preparation method thereof

    CN109939007A